2006
DOI: 10.1128/aem.72.3.1810-1816.2006
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Cryptosporidium Oocysts in Streambeds

Abstract: The transfer of Cryptosporidium oocysts from the surface water to the sediment beds of streams and rivers influences their migration in surface waters. We used controlled laboratory flume experiments to investigate the deposition of suspended Cryptosporidium parvum oocysts in streambeds. The experimental results demonstrate that hydrodynamic interactions between an overlying flow and a sediment bed cause oocysts to accumulate in the sediments and reduce their concentrations in the surface water. The associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 40 publications
4
50
0
1
Order By: Relevance
“…High concentrations of microorganisms that are typically associated with sewage were observed in this analysis, but it is difficult to definitively relate sediment concentrations to CSO discharge events without additional data. Previous studies have demonstrated that CSOs can and do impact the pathogen load in the sediment near the outfall (15,16,46,48,49,80). One important difference between these studies and this analysis is that prior studies usually addressed a single CSO.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…High concentrations of microorganisms that are typically associated with sewage were observed in this analysis, but it is difficult to definitively relate sediment concentrations to CSO discharge events without additional data. Previous studies have demonstrated that CSOs can and do impact the pathogen load in the sediment near the outfall (15,16,46,48,49,80). One important difference between these studies and this analysis is that prior studies usually addressed a single CSO.…”
Section: Discussionmentioning
confidence: 59%
“…While the exposure scenarios included in this assessment were focused primarily upon direct and/or indirect ingestion of water during a variety of activities (e.g., boating, picnicking, fishing, and swimming), many of these activities would also involve direct contact with sediments as well as the water. As sediments may act as a reservoir for pathogens (16,18,40,45,46,48,80), it is important that they, too, be evaluated to determine if they pose a potential risk to human health.…”
mentioning
confidence: 99%
“…A 3-log reduction in the infectivity of PV1 was observed in 14 days in seawater having marine sediments, whereas such a reduction was observed in 4 days in seawater without sediments (23). These results suggest that environmental sediments have a protective effect on pathogens (1,20), and the association of pathogens with environmental sediments cannot be ignored when considering the fate of pathogens in water environments (22).…”
mentioning
confidence: 89%
“…Bacterial (Mycobacterium avium [29] and Clostridium botulinum type E [19]), protozoan (Cryptosporidium species [22]), and viral (enterovirus [EV] [5,13,15], hepatitis A virus [HAV] [6,14], and rotavirus [6]) pathogens have been detected in environmental sediments. Whittington et al reported previously that M. avium in sediments from a dam lake survived 12 to 26 weeks longer than it did in a water column (29).…”
mentioning
confidence: 99%
“…[2] The deposition of colloidal particles in a porous medium is relevant in a broad range of environmental and geophysical problems, such as oil extraction [Moghadasi et al, 2004], subsurface contaminant transport [Kretzschmar et al, 1999], siltation of streambeds [Packman et al, 2000], transmission of pathogens in surface and subsurface waters [Searcy et al, 2006], and water treatment involving filtration in both granular beds and membranes [Elimelech et al, 1995]. Filtration models, summarized by [McDowell-Boyer et al, 1986;Elimelech et al, 1995;Tufenkji and Elimelech, 2004], normally assume fixed pore geometry and parameterize deposition rates in terms of the size ratio between mobile suspended particles and pore spaces.…”
Section: Introductionmentioning
confidence: 99%